Observation of intrinsic dark exciton in Janus-MoSSe heterosturcture induced by intrinsic electric field. (10th September 2018) - Long, Chen; Gong, Zhi-Rui; Jin, Hao; Dai, Ying
Abstract: The nature of exciton in heterostructure exhibits distinct properties, which makes heterostructure a promising candidate for valleytronic and optoelectronic applications. Therefore, understanding of exciton behaviour in heterostructure is the key approach to design novel devices. Here, we investigate the electronic properties including quasiparticle-energy calculations (on the level of the GW approximation) and optical properties (on the level of the Bethe–Salpeter equation) of Janus-MoSSe based heterostructure. Our results show that the build-in electric field caused by spontaneous polarization of Janus-MoSSe monolayer can significantly affect the interlayer interactions within the heterostructure, giving rise to a bright-to-dark exciton transition. To shed light on this phenomenon, a theoretical model is developed, which illustrates that the dark exciton can be ascribed to a coherence cancellation at the band edge positions induced by the strong interlayer coupling. Our findings may provide a new way for modulating and developing of van der Waals heterostructure that have applications in valleytronic and optoelectronic devices.